Physical, Elastic and Thermal Characterization of Ni-Cd Nano Ferrites: Elastic and Thermal Characterization of Ni-Cd - Maqsood, Asghari; Arshad, M. (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
The soft spinel ferrite system Ni1-xCdxFeO4 (x=0.0, 0.2, 0.4, 0.6) have been synthesized by the coprecipitation method. The prepared samples are characterized by the x-ray diffraction (XRD) and FTIR techniques. The XRD data have been used to obtain lattice constants, average crystallite size, specific surface area, dislocation density and strain of the nanoferrites. The data also provided the cation distribution, indicating that Fe3+ occupies both the A and B-sites. The elastic properties of this system are studied through infra-red spectroscopy and XRD data. The force constants for tetrahedral (kt) and octahedral (k0) sites are estimated along with the Poisson’s ratio and the Debye temperature (ѲD).